2021
DOI: 10.1186/s12917-021-03023-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gentamicin and cisplatin-induced kidney damage mediated via necrotic and apoptosis genes in albino rats

Abstract: Background Gentamicin (GM) is a low-cost, low-resistance antibiotic commonly used to treat gram-negative bacterial diseases. Cisplatin (Csp) is a platinum-derived anti-neoplastic agent. This experiment aimed to identify the early signs of gentamicin and cisplatin-induced nephrotoxicity in rats. Thirty Wistar rats were divided into three groups of 10: a control group, which received no treatment; a gentamicin group administered by a dose of (100 mg/kg, IP) for 7 consecutive days, and a cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
(61 reference statements)
3
5
0
Order By: Relevance
“…In this study, GM upregulated Bax and TNF-α, and downregulated Bcl-2 expression. Similar findings confirmed the same effects of GM administration (Abouzed et al 2021). SO, and/or NAC addition with GM restored Bax, Bcl-2 and TNF-α towards control group.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In this study, GM upregulated Bax and TNF-α, and downregulated Bcl-2 expression. Similar findings confirmed the same effects of GM administration (Abouzed et al 2021). SO, and/or NAC addition with GM restored Bax, Bcl-2 and TNF-α towards control group.…”
Section: Discussionsupporting
confidence: 84%
“…The proteins Bax and Bcl-2 play important roles, with Bax acting as a pro-apoptotic factor and Bcl-2 acting as an antiapoptotic factor. Furthermore, TNF-α activation causes oxidative stress and renal inflammation (Abouzed et al 2021). In this study, GM upregulated Bax and TNF-α, and downregulated Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Several studies have demonstrated the molecular mechanism by which GTN induce renal injury. This is seen to include renal tubular damage leading to necrosis and glomerular congestion, subsequently causing renal dysfunction [8]. Furthermore, reports show that GTN increases serum liver enzymes and induces histological lesions, reflecting its hepatotoxic effects.…”
Section: Introductionmentioning
confidence: 99%